Tendering and evaluation process enhancement for sustainable procurement in public sector of Bangladesh - Abdin, Md Jayanal (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2022.